Diagnóstico de la gestión administrativa del Distrito de Educación 13D12 Rocafuerte-Tosagua, período 2021-2022 - García Moreira, Karla Doménica (2022)
The present research work was carried out with the objective of diagnosing the administrative management of the Education District 13D12 Rocafuerte-Tosagua, period 2021-2022. Therefore, methods such as inductive, deductive and analytical-synthetic were used, which allowed the construction of true data of the demonstrated facts; in turn, a structured interview with the legal representative of the institution was used as an information collection technique, in parallel, efficiency and effectiveness indicators were applied to the goals, times and budgets of the activities of the 2021 Annual Operating Plan. In The results evidenced that there are 36 activities of excellent and good performance as planned, then, two were detected at a regular level of execution, and finally, five of a fulfillment well below the programmed goal in the provision tasks resources necessary for the normal operation of institutions, and administration and management of goods and services in electricity, drinking water, and security and surveillance. In short, an improvement action plan was designed that responds to strategic initiatives to correct and mitigate the aspects found as weaknesses.